2009
DOI: 10.1606/1044-3894.3927
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Stressors in a Population of Kinship Caregivers: Implications for Caseload Management and Administration

Abstract: This article presents the results from 77 interviews with kinship caregivers participating in the child-only component of the TANF program. The authors interviewed caregivers using the Strengths and Stressors Tracking device (SSTd). Key findings include: most caregivers and their families possess significant strengths that can be used in a strengths-based approach to case management; environmental stress-an acknowledged ecological correlate with potential for abuse and neglect-is an area of strength; and perma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It was at this point that the authors began developing additional questions that they felt would address the areas of social empathy and commitment to aiding those living in poverty; areas not addressed by Atherton et al Over time 21 new questions were developed that drew upon a review of the literature (Coryn, 2002;Cozzarelli et al, 2001;Mehrabian & Epstein, l972), the authors' own experiences in working with the poor and in conducting research with impoverished populations (Blair, 2010;Blair, Taylor, & Rivera, 2009) and feedback from students in classes taught by the authors. The new questions developed for use in the UPPTS build upon the concepts of a lack of social empathy (Segal, 2007) and cognitive distancing (Lott, 2002) as principal reasons why people fail to do more to help the poor via either direct action or support for programs that will aid the poor.…”
Section: Theoretical Considerations and The Need For An Improved Tracmentioning
confidence: 99%
See 2 more Smart Citations
“…It was at this point that the authors began developing additional questions that they felt would address the areas of social empathy and commitment to aiding those living in poverty; areas not addressed by Atherton et al Over time 21 new questions were developed that drew upon a review of the literature (Coryn, 2002;Cozzarelli et al, 2001;Mehrabian & Epstein, l972), the authors' own experiences in working with the poor and in conducting research with impoverished populations (Blair, 2010;Blair, Taylor, & Rivera, 2009) and feedback from students in classes taught by the authors. The new questions developed for use in the UPPTS build upon the concepts of a lack of social empathy (Segal, 2007) and cognitive distancing (Lott, 2002) as principal reasons why people fail to do more to help the poor via either direct action or support for programs that will aid the poor.…”
Section: Theoretical Considerations and The Need For An Improved Tracmentioning
confidence: 99%
“…Review of the survey items by content experts: The authors have extensive experience in both direct practice and in conducting research with impoverished populations (Blair et al, 2009). Pilot testing: a draft of the UPPTS was given to 20 undergraduate students who were enrolled in an undergraduate course being taught by one of the authors.…”
Section: Procedures In Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinship caregivers are generally grandparents, aunts, uncles or cousins who take over the role of foster parents for the offspring of immediate or extended family members [26]. Differently from non-relative foster care, kinship care allows the preservation of the child's blood ties, thus providing children with a more stable family context [27]; this, on the other hand, implies that kin carers need to contain and minimize the contact and negative influence of abusive birth parents upon the child to a greater extent compared to non-relative foster parents [28]. Moreover, from an institutional point of view, they are less closely monitored and regulated by state child-welfare departments than non-relative foster parents; this reflects in a heightened need of standards, guidelines and proper training [28] to help them deal with all the difficulties and issues of foster children, which nonetheless are scarcely provided by the welfare system [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of kinship caregivers that assessed strengths using the Strengths and Stressors Detection device (Berry, Cash, & Mathieson, 2003), most families in their random sample of kinship care providers showed strengths in the important domains of environment, social support, caregiver traits, and child well-being. In addition, that measure picked up on some of the same indicators this study showed were important to stability of placements such as few marital problems, a stable marital relationship, mutual support, and appropriate expectations for child behavior (Blair, Taylor, & Rivera, 2009).…”
Section: Discussionmentioning
confidence: 99%